Canada Should Move Toward Adopting Harmonized Evidence-Based OELs to Consistently and Adequately Protect Workers. Issue 4 (18th December 2020) - Barn, Prabjit; Keefe, Anya R; Slot, Nicole; Jardine, Katherine J; Ziembicki, Stephanie; Telfer, Joanne; Palmer, Alison L; Peters, Cheryl E
Abstract: Due to the way occupational exposure limits (OELs) are set in Canada, workers across the country are not equally and adequately protected from harmful workplace exposures. This disparity is illustrated in the case of exposure to diesel engine exhaust (DEE). Based on the findings of a recent pan-Canadian and international scan of OELs for DEE, we recommend that Canada overcome these current disparities by moving towards harmonized, evidence-based OELs. To achieve this, Canada should adopt a centralized framework for setting OELs that considers the most recent scientific evidence as well as feasibility of implementation in the Canadian context. We assert that harmonizing OELs across Canada would allow for expertise and resources to be consolidated and is a crucial step to ensuring that all workers are consistently protected from harmful workplace exposures.